Pengaruh Kepercayaan Merek, Komitmen, Kepuasan Nasabah Dan Kualitas Pelayanan Terhadap Loyalitas Nasabah Pada PT. Bank Central Asia Tbk. Cabang Tenggarong - Sugeng Raharjo; Tria Wulandari (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2022)
Abstract:The Problems that occurred at PT. Bank Central Asia Tbk. Tenggarong Branch, there are some problems that must be fixed such as Lack of Customer Confidence where there is a passive account and minimum balance, that is with initial deposit balance Rp.500.000, and Balance held / minimum of Rp.50.000, and where the Passive Account (Dormaint) will be closed Themselves within 3 months, and the Bank has not been able to provide more facilities to its customers, which is a parking facility that is not adequate enough to park the vehicle Customer, as well as the place for transactions between the Customer With the bank has not been maximized, ATM and Office are made into one room. So lack of Attention from the bank, on the services provided to customers to use the Service back.The main objective of this research is to find out how much influence Brand Trademark, Commitment, Customer Satisfaction, and Service Quality affect Customer Loyalty that already exists at PT. Bank Central Asia Tbk. Tenggarong Branch. Keywords: Brand Trust, Commitment, Customer Satisfaction, and Service Quality Against Customer Loyalty